Anemia in pregnant mothers and the apgar score of newborn babies at secondary refferal hospital, Bali - Cokorda Agung Prasetya Dwipayana; I Gusti Ngurah Made Bayuningrat; Pande Ayu Naya Kasih Permatananda; Asri Lestarini (Institute of Computer Science (IOCS), 2023)
Low hemoglobin levels due to anemia in pregnancy can affect the baby's APGAR score. The purpose of this study was to determine the relationship between anemia in pregnant women and the APGAR score of newborns at the Sanjiwani Hospital, Gianyar. This research is an analytic observational study with a cross sectional research design. This study used medical records data of patients who gave birth vaginally and had normal births, did not have low birth weight, had normal first and second stages of labor, and had complete laboratory data on hemoglobin levels and APGAR scores. Data on mothers experiencing obstetric complications other than anemia were excluded from this study. Data were analyzed by univariate and bivariate using Chi-square hypothesis test. From 140 samples of pregnant women, there were 78 (55,7%) samples of pregnant women who had anemia and 62 (44,3%) samples of pregnant women was not had anemia. Bivariate analysis showed that there was a significant relationship between anemia in pregnant women and the APGAR score of newborns with p value = 0.001 (p <0.05). We concluded that there was a relationship between anemia in pregnant women and the APGAR score of newborns at the Sanjiwani Hospital, Gianyar.